WATER QUALITY IN BROILER CHICKENS FARMS TOWARDS THE NUMBER OF COLIFORM AND ESCHERICHIA COLI BACTERIA - Lusandika, Eggy Hidta; Suarjana, I Gusti Ketut; Suada, I Ketut (Buletin Veteriner Udayana; Vol. 9 No. 1 Pebruari 2017, 2017)
This study aims were to determine the number of  Coliform and Escherichia coli bacteria in drinking water of broiler chickens farm in the Mangesta Village, Penebel Sub-District, Tabanan.  This study used a randomized block design from three sampling sites which were Beji (the water springs), water reservoir, and drinking place livestock, and had nine times repetition in each group. The number of Coliform and Escherichia coli bacteria was calculated by the method of spread. The data result from Coliform and Escherichia coli bacteria were analyzed using Analysis of Variance, followed by Duncan's Multiple Range Test. The research number of Coliform bacteria at Beji (water springs), water reservoir, and the drinking plate were 19768 x 10 5 CFU/100 ml, 11222 x 10 5 CFU/100 ml, 30957 x 10 5 CFU/100 ml and the number of Escherichia coli were 9233 x 10 5 CFU/100 ml, 3457 x 10 5 CFU/100 ml, and 19657 x 10 5 CFU/100 ml. Statistically, the number of Escherichia coli and Coliform in drinking place was significantly higher than the Beji (water springs) and water reservoir.
Keywords: Coliform, Escherichia coli, Kualitas air, Peternakan ayam broiler